(untitled) (Homoeopathy for All, 2023)
Life is composed of body, mind, and spirit. This is the trinity of life. Body and tissues are not life they are only the channels through which life functions. The material body derives its life from an immaterial, autocratic, spiritual, dynamic thing called ‘VITAL FORCE’. It maintains the harmony of life producing normal sensations and functions.